The influence of a vibrating rectangular piston on the acoustic power radiated by a rectangular plate - ZAWIESKA, Wiktor M.; RDZANEK, Wojciech P. (Archives of Acoustics, 2007)
The equation of motion of a flat simply supported rectangular plate has been solved. The plate has been excited by a surface force. The influence of the acoustic pressure radiated by the plate on its vibrations has been included. The corresponding sound pressure distributions have been presented as their backward Fourier transforms. The acoustic active and reactive sound power has been computed including the influence of the sound pressure radiated by the piston. The acoustic mutual sound power of both sources has also been presented.